Resúmenes de novedades - Foro Internacional, Revista (Foro Internacional, 2023)
David Lindsey, Delegated Diplomacy: How Ambassadors Establish Trust in International Relations, New York, Columbia University Press, 2023, 376 pp. Paul Tucker, Global Discord: Values and Power in a Fractured World Order, Princeton, New Jersey, Princeton University Press, 2022, 552 pp. Taylor C. Boas, Evangelicals and Electoral Politics in Latin America: A Kingdom of this World, New York, Cambridge University Press, 2023, 340 pp. Matari Pierre, El Leviatán domesticado: las relaciones entre el capital financiero y el Estado, Ciudad de México, UNAM, Instituto de Investigaciones Sociales, 2022, 376 pp. Samuel Issacharoff, Democracy Unmoored: Populism and the Corruption of Popular Sovereignty, New York, Oxford University Press, 2023, 296 pp. Lorenza B. Fontana, Recognition Politics: Indigenous Rights and Ethnic Conflict in the Andes, Cambridge, UK, Cambridge University Press, 272 pp Roberto Mangabeira Unger, Governing the World Without World Government, London, UK, Verso, 2022, 96 pp. Rolando Cordera y Alicia Ziccardi (comps.), Las políticas sociales de México. Derechos constitucionales, arquitectura institucional, 2000-2018, Ciudad de México, Siglo XXI, 2022, 547 pp. Enzo Traverso, trad. Horacio Pons, Revolución: Una historia intelectual, Madrid, Ediciones Akal, 2022, 528 pp. Juliette Galonnier, Stéphane Lacroix y Nadia Marzouki, Politiques de lutte contre la radicalisation, Paris, Sciences les Presses, 2022, 188 pp.